Sensitive written hedgehog PICture Naming and Immediate Recall (PICNIR) as a valid and brief test of semantic and short-term episodic memory for very mild cognitive impairment - Bartos, Ales; Diondet, Sofie (Journal of Alzheimer's disease, 2024)
BACKGROUND: Semantic and short-term episodic memory are impaired in some brain disorders including Alzheimer's disease. OBJECTIVE: Development and validation of an almost self-administered, but cognitively demanding four-minute test identifying very mild cognitive impairment (vMCI). METHODS: The innovative hedgehog PICture Naming and Immediate Recall (PICNIR) consisted of two parts. The first task was to write down the names of 20 black-and-white pictures to evaluate long-term semantic memory and language. The second task involves immediate recall and writing the names of as many previously named pictures as possible in one minute. The PICNIR is assessed using the number of naming errors (NE) and correctly recalled picture names (PICR). The PICNIR and a neuropsychological battery were administered to 190 elderly individuals living independently in the community. They were divided into those with vMCI (n = 43 with Montreal Cognitive Assessment (MoCA) 24 ± 3 points) and sociodemographically matched cognitively normal (CN) individuals (n = 147 with MoCA 26 ± 3). Both subgroups had predicted mean Mini-Mental State Examination scores of 28-29 points. RESULTS: Compared to CN, vMCI participants made more NE (0.3 ± 0.6 versus 0.6 ± 0.9; p = 0.02) and recalled fewer PICR (8.9 ± 2.2 versus 6.8 ± 2.2; p < 0.000001). Discriminative validity was satisfactory using the area under the ROC curve (AUC): 0.76 for PICR, 0.74 for MoCA, 0.67 for MoCA-five-word recall, and 0.59 for NE. The AUCs of PICR and MoCA were comparable and larger than those of MoCA five-point recall or NE. Logical Memory scores, RAVLT scores, Digit symbol, and animal fluency correlated with PICR. CONCLUSIONS: The picture-based PICNIR is an ultra-brief, sensitive cognitive test valid for assessing very mild cognitive impairment. Its effectiveness should be validated for other languages and cultures.
Keywords: Male; krátkodobá paměť; Semantics; kognitivní dysfunkce; testy pro posouzení mentálních funkcí a demence; sémantika; Aged; mužské pohlaví; senioři; Memory, Episodic; Cognitive Dysfunction; Mental Recall; reprodukovatelnost výsledků; Mental Status and Dementia Tests; Reproducibility of Results; rozpomínání; Neuropsychological Tests; senioři nad 80 let; lidé; ženské pohlaví; Humans; Aged, 80 and over; neuropsychologické testy; Female; epizodická paměť; Memory, Short-Term